2016
DOI: 10.1097/md.0000000000004628
|View full text |Cite
|
Sign up to set email alerts
|

Less wound complications of a sinus tarsi approach compared to an extended lateral approach for the treatment of displaced intraarticular calcaneal fracture

Abstract: Background:We conducted a prospective randomized clinical trial to compare the clinical and radiological outcomes of the sinus tarsi and extended lateral approaches for the surgical treatment of displaced intraarticular calcaneal fractures.Methods:Between January 2009 and January 2014, patients with displaced intraarticular calcaneal fracture were randomly assigned to receive surgical treatment by the sinus tarsi approach or the extended lateral approach using block randomization. We recorded and analyzed data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…Reported complications rate related to calcaneus varied quite widely according to literature. Rate of complications for the ELA ranged from 3.5% to 31.2% and from 5% to 8.49% for the STA . Complication rate of 3.5% in 57 Sanders type III calcaneal fractures treated with ELA was reported by Cao et al George et al even reported that they had never encountered any wound dehiscence, or wound infection during an 18‐year period using a minimally invasive approach for ORIF for DIACFs .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Reported complications rate related to calcaneus varied quite widely according to literature. Rate of complications for the ELA ranged from 3.5% to 31.2% and from 5% to 8.49% for the STA . Complication rate of 3.5% in 57 Sanders type III calcaneal fractures treated with ELA was reported by Cao et al George et al even reported that they had never encountered any wound dehiscence, or wound infection during an 18‐year period using a minimally invasive approach for ORIF for DIACFs .…”
Section: Discussionmentioning
confidence: 93%
“…The ELA is the gold standard of operative approach for calcaneus fractures and is applied for any type of Sanders fracture. However, the rate of complications, including infection, dehiscence and skin necrosis was high and was reported to range from 13.3% to 31.2% …”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported good clinical and radiographic results for this approach and a low incidence of complications although studies vary with respect to approach site, length of incision, and fixation method 41718192021222829303132. In addition, in the majority of studies, the accuracy of posterior facet reduction was evaluated using Böhler's and Gissane's angles in plain radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…The primary concern with this approach is a high complication rate. [36][37][38][39][40][41][42][43] Some techniques can be employed to decrease the risk of complications related to this approach. For example, the corner of the incision should be curved to avoid significant wound complications.…”
Section: Conservative Treatment Vs Open Reduction and Internal Fixationmentioning
confidence: 99%
“…Minimally invasive techniques have been proposed for displaced intra-articular calcaneal fractures with the aim of potentially lowering wound complication rates and improving overall outcomes. 42,61 Various minimally invasive approaches, such as the Palmer approach, 34 Smile incision, 62 Ollier approach, 63 sinus tarsi approach, 46,64,65 and minimally invasive longitudinal approach, 66 have been introduced to minimize the wound complication rate.…”
Section: Internal Fixation Of Displaced Intraarticular Calcaneal Fracmentioning
confidence: 99%